2022
DOI: 10.1186/s12909-022-03938-y
|View full text |Cite
|
Sign up to set email alerts
|

Online learning for continuous professional development of healthcare workers: an exploratory study on perceptions of healthcare managers in Rwanda

Abstract: Background Due to outbreaks of new diseases, development of new treatment regimens and requirement of evidence-based practice, health professionals continuously need to acquire updated knowledge and skills. This type of learning is known as continuous professional development (CPD). The scarcity of skilled health care professionals in developing countries further increases the need of CPD. Traditionally, face-to-face approach has been preferred as the best mode of CPD. Currently, health profess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…We encourage cultural safety trainers to invest in training formats such as podcasts, videos, virtual reality experiences and face to face workshops. While managers consider didactic online training modules to be cost effective and time efficient, healthcare providers wishing to improve the delivery of culturally safe care perceive online training as an ineffective time-wasting exercise that contributes to loss of collegiality and merely ticks boxes for institutional reports [ 32 , 47 , 84 , 85 ]. Good retention at Ask the Specialist Plus over the weeks of program delivery, despite extreme pressures of clinical work compounded during the periods of delivery by COVID measures, attest to the level of interest and appeal of the program.…”
Section: Discussionmentioning
confidence: 99%
“…We encourage cultural safety trainers to invest in training formats such as podcasts, videos, virtual reality experiences and face to face workshops. While managers consider didactic online training modules to be cost effective and time efficient, healthcare providers wishing to improve the delivery of culturally safe care perceive online training as an ineffective time-wasting exercise that contributes to loss of collegiality and merely ticks boxes for institutional reports [ 32 , 47 , 84 , 85 ]. Good retention at Ask the Specialist Plus over the weeks of program delivery, despite extreme pressures of clinical work compounded during the periods of delivery by COVID measures, attest to the level of interest and appeal of the program.…”
Section: Discussionmentioning
confidence: 99%
“…A study of emergency medicine physicians in the US showed that 65.62% of respondents would like to study via video, 13.98% via classroom (instructor-led training), and 5.68% via live webinars [ 27 ]. Additionally, a convergence mixed method study in Rwanda showed that participants preferred blended learning the most (online and face-to-face learning combined) [ 28 ]. This minor difference might be from the varied learning style preferences in other countries, in addition to challenges for delivering online CPD content in some areas of the world.…”
Section: Discussionmentioning
confidence: 99%
“…In the Technology Acceptance Model, external control is de ned as the degree to which an individual believes that the organization can provide the necessary support. Previous studies on electronic devices and internet connectivity have produced varied ndings: certain health centers in Rwanda are equipped with computers and have fast and stable internet connections, whereas others lack su cient electronic devices, and face challenges with both the speed and stability of their internet [24,25]. In this study, participants were provided with tablets and internet access, and we did not evaluate the capability of existing electronic devices and the internet infrastructure to support VP cases as a CPD approach.…”
Section: Discussionmentioning
confidence: 99%